Biochar enriched with organic fertilizer improves the survival and growth rate of Anthocepalus cadamba seedlings planted on degraded spodosols - Syahrinudin Syahrinudin; Wahjuni Hartati; Triyono Sudarmadji; Nurman Krisdianto; Ibrahim Ibrahim (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Syahrinudin, Hartati W, Sudarmadji T, Krisdianto N, Ibrahim. 2019. Biochar enriched with organic fertilizer improves the survival and growth rate of Anthocepalus cadamba seedlings planted on degraded spodosols. Biodiversitas 20: 3741-3750. The application of biochar for the improvement of soil properties and fertility has drawn enormous interest worldwide nowadays and numerous application options are now available. This research was aimed to evaluate the effects of the application of biochar and organic fertilizers on the survival and growth of Anthocepalus cadamba seedlings planted on degraded spodosols soil on bioassay trial in the nursery. Bioassay trial was carried out in the nursery of Faculty of Forestry, Mulawarman University, Samarinda, Indonesia, employing a 2-factors Completely Randomized Design (CRD) with factor 1 was the rate of biochar application (i.e. six levels of treatment: 0 (control), 2, 5, 10, 25 and 100%v of biochar), and factor 2 (enrichment of organic fertilizers, i.e. with enrichment and without enrichment), and each treatment combination had 3 replications. The results showed that biochar application alone improved height and diameter growth rate of A. cadamba seedlings by 253% and 116% of control treatment (without biochar), respectively. Enrichment of organic fertilizers gave further improvement in height and diameter growth rate of A. cadamba seedlings to 386% and 150% of control treatment (without biochar), respectively. Furthermore, biochar application improved survival and biomass growth rate of the seedlings. Enrichment of organic fertilizers into biochar improved not only seedling growth rate but also more interestingly the carrying capacity of spodosols to biochar application rate. We concluded that biochar application complemented with enrichment of organic fertilizers on spodosols is highly promising for the improvement of both soil carbon sequestration and plant growth performance.